2014
DOI: 10.1016/j.jacc.2014.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Release and Capture of Bioactive Oxidized Phospholipids and Oxidized Cholesteryl Esters During Percutaneous Coronary and Peripheral Arterial Interventions in Humans

Abstract: Objective To assess whether oxidized lipids are released downstream from obstructive plaques following percutaneous coronary and peripheral interventions using distal protection devices. Background Oxidation of lipoproteins generates multiple bioactive oxidized lipids that affect atherothrombosis and endothelial function. Direct evidence of their role during therapeutic procedures, which may result in no-reflow phenomenon, myocardial infarction and stroke, is lacking. Methods The presence of specific oxidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 44 publications
1
92
0
Order By: Relevance
“…As described previously in both humans and nonhuman primates, our data show that cynomolgus monkeys had highly variable hepatic mRNA expression levels ( 44,45 ). Results from this events, lending evidence that the content of pro-infl ammatory OxPLs are key determinants of atherogenic risk mediated by Lp(a) (37)(38)(39)(40)(41)(42).…”
Section: Pharmacology Of Isis-apo(a) Rx In Lean Cynomolgus Monkeyssupporting
confidence: 81%
“…As described previously in both humans and nonhuman primates, our data show that cynomolgus monkeys had highly variable hepatic mRNA expression levels ( 44,45 ). Results from this events, lending evidence that the content of pro-infl ammatory OxPLs are key determinants of atherogenic risk mediated by Lp(a) (37)(38)(39)(40)(41)(42).…”
Section: Pharmacology Of Isis-apo(a) Rx In Lean Cynomolgus Monkeyssupporting
confidence: 81%
“…We speculate that the OxPLs on the r-apo(a) constructs are likely derived from OxPLs generated from apoptotic cells in cell culture ( 52 ). In vivo, OxPLs on Lp(a) may be derived from hepatocytes during Lp(a) assembly, particularly if there is enhanced hepatocyte oxidative stress, such as in nonalcoholic steatohepatitis ( 53 ), or transferred to Lp(a) in plasma from atherosclerotic plaques, as suggested by prior human studies in patients undergoing percutaneous coronary intervention ( 22,54 ). Importantly, however, our studies of OxPLs on apo(a), expressed both in cell culture and found in mouse plasma, show a similar dependence on an intact LBS in KIV 10 , suggesting that the OxPLs acquired by apo(a) in vitro are a relevant model for those acquired by the apo(a) component of Lp(a) in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…ROS play a role in the attack against microbial pathogens by host cells (Imlay, 2013), time-dependent death of dormant seeds (Lee et al, 2010), human diseases (Coyle and Puttfarcken, 1993;Giugliano et al, 1996), in aging (Sohal and Weindruch, 1996;Sohal et al, 2002), and in signaling processes (Gilroy et al, 2016;Mignolet-Spruyt et al, 2016) Unlike oxidized fatty acids (FAs), oxidized lipids are hardly available commercially. Targeted liquid chromatography-mass spectrometry (LC-MS) analysis of oxidized lipids using authentic standards is not very common (Hui et al, 2010;Ravandi et al, 2014). Often, oxidized lipids are detected using tandem mass spectrometry (MS/MS), where the collision-induced products of precursor ions (PRs) are scanned for fragments or neutral losses (NLs) that correspond to oxidized acyl residues expected in oxidized lipids (Spickett and Pitt, 2015), and in some cases, higher resolution MS/MS spectra are provided to support the identification (Buseman et al, 2006;Vu et al, 2012).…”
mentioning
confidence: 99%
“…Targeted liquid chromatography-mass spectrometry (LC-MS) analysis of oxidized lipids using authentic standards is not very common (Hui et al, 2010;Ravandi et al, 2014). Often, oxidized lipids are detected using tandem mass spectrometry (MS/MS), where the collision-induced products of precursor ions (PRs) are scanned for fragments or neutral losses (NLs) that correspond to oxidized acyl residues expected in oxidized lipids (Spickett and Pitt, 2015), and in some cases, higher resolution MS/MS spectra are provided to support the identification (Buseman et al, 2006;Vu et al, 2012).…”
mentioning
confidence: 99%